Pengaruh Deadline dalam Memacu Semangat Mahasiswa untuk Memenuhi Tugas KKNI: Penelitian - Akbar Fahlevi; Deni Theresya Sitohang; Karunia Lestari; Safira Aurelia Irawan; Roza Thohiri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research aims to analyze the influence of deadlines on students' enthusiasm in completing tasks based on the Indonesian National Qualifications Framework (KKNI). This research used a quantitative method with a survey technique through questionnaires distributed to 101 students from various study programs. The research results showed that the majority of students (79.2%) agreed and strongly agreed that deadlines motivated them to complete tasks, and 74.2% felt more productive with deadlines. However, 57.4% of respondents also admitted to often procrastinating on tasks before approaching the deadline, and 41.6% felt that deadlines could cause stress. Data analysis showed that deadlines played a significant role as an external motivator for students in completing KKNI-based tasks, in line with Steel's theory of procrastination and Schraw, Wadkins, & Olafson's theory of learning motivation. Nevertheless, the tendency for procrastination and stress due to deadlines still needs